Glyceridic and Unsaponifiable Components of Microencapsulated Sacha Inchi (Plukenetia huayllabambana L. And Plukenetia volubilis L.) Edible Oils - Chasquibol Silva, Nancy Ascención (2019)
Sacha inchi (Plukenetia huayllabambana L. and Plukenetia volubilis L.) edible oils were microencapsulated and the lipid fraction of the microparticles was characterized. Hi-cap®, Capsule®, Arabic gum, and the binary combination of Arabic gum + maltodextrin and the ternary combination of Arabic gum + maltodextrin + whey protein isolate, were used as coating materials for the encapsulation process using spray-drying. The surface and the total oils obtained from the microparticles were evaluated in terms of fatty acid composition, minor glyceride polar compounds, polymers, oxidized triglycerides, diglycerides, monoglycerides, and free fatty acids, along with their unsaponifiable components, sterols, and tocopherols. Differences between the original oils and the microencapsulated ones were determined. The most remarkable results included the presence of polymers when there were none in the original oils, the slight loss in ¿3-fatty acids, up to 6%, the loss in tocopherols, in some of the cases around 30%, the maintaining of the phytosterol in their initial levels and the presence of cholesterol in the oils encapsulated with whey protein isolate.